Itinerarios del documental presidencial en Ecuador (Ensayos) - Cortez Guamba, Edgar Washington (2023)
The purpose of this essay is to map documentary film productions related to presidential-political issues in Ecuador; under the premise of glimpsing the tendencies, styles, languages and modalities of representation present in the selected audiovisuals. The elements that structure the investigation rehearse the following order. First, the states of Ecuadorian documentary cinema will be defined, under the descriptive intention of enunciating the transformations, aesthetics and narrative discourses that the documentary field experiences. Second, an audiovisual cartography of audiovisual productions with presidential-political themes is proposed; The objective of tracing the film documents is to define the insistent relationship between documentary-politics and memory, understanding audiovisual representation as a discursive-visual resource that reaffirms the forms of representation and social memory. Finally, the considerations will expose the findings evidenced from the cartographic and descriptive exercise carried out apart from the documentaries described.